2004
DOI: 10.1111/j.1464-410x.2004.04787.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin‐like growth factor‐1 on apoptosis of rat testicular germ cells induced by testicular torsion

Abstract: OBJECTIVE To investigate the possible protective role of insulin‐like growth factor‐1 (IGF‐1, reported to have a protective effect in experimental models of hypoxic ischaemia), and the involvement of apoptotic cell death in a model of torsion/detorsion of the rat testis. MATERIALS AND METHODS Adult male Wistar rats were divided into five groups of five rats each. Group 1 underwent a sham operation as a control; in group 2 the testis was twisted and in group 3 then untwisted; in group 4 IGF‐1 was injected subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The importance of ROS in the pathway to testicular T/D injury is also supported by the finding that oxygen radical scavengers prevent or ameliorate testicular loss of spermatogenesis after repair of testicular torsion in several studies [17,19,24]. In our study, we observed that the level of ipsilateral testicular MDA was significantly increased in the T/D and the T/D + vehicle groups.…”
Section: Discussionsupporting
confidence: 88%
“…The importance of ROS in the pathway to testicular T/D injury is also supported by the finding that oxygen radical scavengers prevent or ameliorate testicular loss of spermatogenesis after repair of testicular torsion in several studies [17,19,24]. In our study, we observed that the level of ipsilateral testicular MDA was significantly increased in the T/D and the T/D + vehicle groups.…”
Section: Discussionsupporting
confidence: 88%
“…Another study showed that IGF-1 also stimulated the differentiation of type A spermatogonia using the mouse testicular fragments [55]. IGF-1 was also reported to protect rat germ cells from apoptosis induced by testicular torsion [56]. These early studies provide valuable clues for the roles of IGF-1R signaling in spermatogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, MgSO 4 , propofol, epidermal growth factor, insulin-like growth factor 1, 3-aminobenzamide, human chorionic gonadotropin, vasoactive intestinal peptide, and ginkgo biloba [28] were reported to be useful in TT [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 98%